Realizing the gravity of the simulation: adaptation to simulated hypogravity leads to altered predictive control - Rock, Chase G.; Kwak, Samuel T.; Luo, Angela; Yang, Xiao; Yun, Kristy; Chang, Young-Hui (Frontiers in Physiology, 2024)
Accurate predictive abilities are important for a wide variety of animal behaviors. Inherent to many of these predictions is an understanding of the physics that underlie the behavior. Humans are specifically attuned to the physics on Earth but can learn to move in other environments (e.g., the surface of the Moon). However, the adjustments made to their physicsbased predictions in the face of altered gravity are not fully understood. The current study aimed to characterize the locomotor adaptation to a novel paradigm for simulated reduced gravity. We hypothesized that exposure to simulated hypogravity would result in updated predictions of gravity-based movement. Twenty participants took part in a protocol that had them perform vertically targeted countermovement jumps before (PRE), during, and after (POST) a physical simulation of hypogravity. Jumping in simulated hypogravity had different neuromechanics from the PRE condition, with reduced ground impulses (p ≤ .009) and muscle activity prior to the time of landing (i.e., preactivation; p ≤ .016). In the 1g POST condition, muscle preactivation remained reduced (p ≤ .033) and was delayed (p ≤ .008) by up to 33% for most muscles of the triceps surae, reflecting an expectation of hypogravity. The aftereffects in muscle preactivation, along with little-to-no change in muscle dynamics during ground contact, point to a neuromechanical adaptation that affects predictive, feed-forward systems over feedback systems. As such, we conclude that the neural representation, or internal model, of gravity is updated after exposure to simulated hypogravity.